The "diaspora" concept in scientific research; SGEM. 3rd International Multidisciplinary Scientific Conference on Social Sciences and Arts; Bk. 3, vol. 2 - Babuta M. N. Marina Nikolaevna; Pershikov A. N. Anatoly Nikolaevich; Nguyen Thi Hong Bach Lien; Anisimov M. V. Maksim Vasiljevich; Shevtsov V. V. Vyacheslav Veniaminovich (History, 2016)
Title screen